The effects of intercropping of sweet corn and groundnut in immature durian orchard on the biological and economic yield indices - Nurin Maisarah Mappah; Borhan Abdul Haya; Muhamad Askari; Ilmas Abdurofi; Dk. Nor Hajijah Ak. Mohiddin; Azwan Awang; Nurul Mayzatul Azwa Jamaludin (UniSE Press, 2025)
Sweet corn (Zea mays convar. saccharata var. rugosa) and groundnut (Arachis hypogaea L.) are important crops with significant nutritional and economic value. However, monoculture practices and land underutilization in immature durian (Durio zibethinus Murr.) orchards present challenges such as soil degradation and reduced productivity. This study evaluated the biological and economic yield indices of intercropping sweet corn and groundnut in immature durian orchards as a sustainable alternative. The research was conducted at the Faculty of Sustainable Agriculture (FSA), Universiti Malaysia Sabah, Sandakan campus, over five months, the experiment employed a randomized complete block design (RCBD) with four treatments: monoculture of sweet corn (T1), monoculture of groundnut (T2), and two intercropping systems with staggered planting times (T3 and T4). Parameters measured included Land Equivalent Ratio (LER), Area Time Equivalent Ratio (ATER), Aggressivity (A), Competitive Ratio (CR), Relative Crowding Coefficient (RCC), Actual Yield Loss (AYL), Monetary Advantage Index (MAI), and Gross Profits (GP). However, results showed that T3 and T4 intercropping systems outperformed monocultures, with T4 yielding the highest fresh weight, MAI, and GP. LER and ATER exceeded 1 in T3 and T4, demonstrating greater land-use efficiency. Sweet corn exhibited higher competitiveness (A and CR) in intercropping systems, while groundnut showed reduced yields under shading. The study concludes that intercropping sweet corn and groundnut in immature durian orchards optimizes land productivity, improves economic returns, and offers a sustainable solution for enhancing orchard management.